STUDENT RETENTION IN ARITHMETIC SEQUENCES AND SERIES LEARNING THROUGH MATH MAZE - Kosasih, Usep; Kusumaningtyas, Sarah; Saputra, Samnur (Program Studi Magister Pendidikan Matematika, Universitas Siliwangi, 2024)
Students' lack of interest in studying mathematics has an impact on their memory of the material taught. Weak memory in understanding the material is one of the obstacles in learning mathematics. This becomes a challenge for educators to find the right learning method. When studying arithmetic sequences and series, a strong memory really helps students' understanding. In this research, the mathematical maze is used as a learning method to strengthen student retention. The aim of the research is to describe the retention of student learning outcomes after mathematics learning assisted by Math Maze on arithmetic sequences and series. This research uses a qualitative approach. The data collection process was carried out by post-test and re-test. Based on the results of data analysis, it was concluded that the retention of student learning outcomes in learning arithmetic sequences and series through the mathematical maze was relatively high. This means that the math maze can be an alternative to learning mathematics.